Years of Schooling, Human Capital and the Body Mass Index of European Females - Giorgio Brunello; Daniele Fabbri; Margherita Fort (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We find that the protective effect of years of schooling on the BMI of European females is non negligible, but smaller than the one recently found for the US. By using individual standardized cognitive tests instead of years of schooling as the measure of education we show that the current focus in the literature on years of schooling is not misplaced. We also investigate whether the response to changes in compulsory education is heterogeneous, and find that the protective effect of schooling is stronger among overweight than among obese females.
Keywords: I12; I21; 330; Obesity; human capital; Europe; Gesundheitsrisiko; Bildungsniveau; Frauenbildung; Frauen; Europa